(untitled) (Al-Qamar, 2019)
The notions of ‘best interest’ and ‘welfare of the child’ have been used since a long in custody cases although the vision of both notions has been changed now by the United Nations Convention on the Rights of the Child 1989. The standards for awarding custody of child and interpretation of the principles of ‘best interest’ and ‘welfare of child’ have been different in all three jurisdictions i.e., Islamic Republic of Pakistan, France, and UK. All three jurisdictions have devised their distinct system of custody or control of children after the separation/divorce of their parents. The different standards and different interpretations entail the different legal systems, social structures and constructions, religion, conventions, customs, and development as well. The standards and interpretations of these notions depend on and are motivated mostly by Islamic law of Sharīʻah in Pakistan while modernism and liberalism in France and United Kingdom.